Budget Institutions for Subnational Fiscal Discipline: Local Fiscal Rules in Post-Crisis EU Countries. - (:unkn) unknown (Springer, 2021)
Fiscal rules are institutional constraints on budget policymakers’ decision-making discretion aimed at fostering prudent fiscal policy, promoting overall fiscal discipline, and ensuring long-term fiscal sustainability. Since the European sovereign debt crisis, fiscal rules have been at the centre of the debate on the EU’s economic governance, the need to strengthen fiscal frameworks and improve policy co-ordination. This chapter outlines the origin, purpose, design, and coverage of local fiscal rules in EU countries over a decade after the 2008 financial crash. It presents a review of the empirical evidence on subnational fiscal rules and their impact and effectiveness on fiscal outcomes. The chapter ends with some concluding remarks and lessons drawn from the experience of fiscal rules across both time and space and outlines how policymakers can learn from this international experience.
Keywords: EU; Ländervergleich; Finanzpolitik; Haushaltspolitik; Wirtschaftspolitik; Regionale Wirtschaftspolitik; Kommunale Wirtschaftspolitik; Gemeindefinanzpolitik; Steuerpolitik; Europäische Union